Insolvency Proceedings and Shareholdings: When ss a Foreign Judgment not a Judgment? Cambridge Gas v. Navigator Holdings Pattni v Ali - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2007)
Rule 40(1) of Dicey, Morris and Collins 1 reads as follows: A court of a foreign country has jurisdiction to give a judgment in rem capable of enforcement or recognition in England if the subject-matter of the proceedings wherein that judgment was given was immovable or movable property which was at the time of the proceedings situate in that country. Its application seems to be simple enough. But the commentary to r 40 warns us, “[t]he question whether a foreign judgment is in personam or in rem is sometimes a difficult one on which English judges have been divided in opinion”. This warning, however, still falls rather short. As two opinions recently handed down by the Privy Council illustrate, r 40(1) raises two distinct issues: one, whether for purposes of recognition or enforcement, a foreign judgment is to be characterized as being in rem or in personam , and two, whether the foreign “judgment” is a judgment at all.